Migration Policies of the Czech and Slovak Republics Since 1989 – Restrictive, Liberal, Integrative or Circular? - Věra Stojarová (Transylvanian Review of Administrative Sciences, 2019)
The author compares the migration policies of the Czech Republic and Slovakia since 1993, including both immigration as well as integration. The text focuses mainly on the autochthonous policies of both countries in regards to labor migration as the main type of migration. Significant immigration is a recent phenomenon in both the Czech Republic as well as Slovakia and neither immigration, nor integration policy belong among the priorities of either state. The Czech Republic seems to be more mature in adopting regulations for better access of foreigners to the labor market. However, when comparing the Czech Republic with the rest of Europe, it belongs to the most restrictive countries in terms of integration as well as in terms of immigration. Given the extremely low ratio of non-EU born adults becoming Czech citizens, the Czech Republic will remain an exclusionary democracy unless it changes either the voting rights or increases the naturalization rates by reducing the conditions for foreigners. Quite interestingly, even though Slovakia lags behind the Czech Republic in terms of integration policies and naturalization rates, it is more inclusive in terms of political rights.